Executed on a technicality: lethal injustice on America's death row - Dow, David (Beacon Press, 2005)
The execution of Carl Johnson -- Cesar Fierro's coerced confession -- Johnny Joe Martinez's fatal five minutes -- Some get released, some get executed -- Innocence is not enough -- Interlude : why does innocence matter? -- How the rule of law became mob rule.